Integrating the Coffee Culture with the Teaching of English - Carmen Tulia Zuluaga Corrales; Margarita María López Pinzón; Josefina Quintero Corzo (Profile: Issues in Teachers' Professional Development)
The present article gives account of the results of a research project developed at the University of Caldas with a group of preservice teachers and advisors. The purpose of the work was to sensitize the academic community about the importance of rescuing the cultural identity of rural school students. To achieve this goal, advisors and preservice teachers innovated the school curriculum by integrating the coffee culture to the English program. The study revealed that preservice teachers became skillful at designing content-based tasks that were more meaningful for the students; likewise, they became more sensitive to the problems that affected rural students and their families. It was also found that these students became aware of the commitment they had with the region and its surroundings; furthermore, because classes were more appealing, their motivation increased significantly.